The Use of Audio Visual Video Media on Understanding the Concept of Disaster Mitigation of Geographic Education Students of Veteran Bangun Nusantara Sukoharjo University - Muh. Husyain Rifa'i (Universitas Veteran Bangun Nusantara, 2020)
The learning of Disaster Mitigation Material needs to be given to student teacher’s candidate, so the college students have the understanding about the importance of disaster Mitigation because Indonesia is included in the Pacific Ring of Fire. This research aims to analyze the understanding of disaster mitigation concept of students before and after given learning material by using Audio Visual Video media to the early level college students. This uses quantitative research with an experimental approach. The population on this research are college students at semester 1 & 3 of Geography Education in the odd semester of 2017/2018 academic year with 24 participants. The data collecting techniques use test, student’s worksheet and questionnaire. Data analysis technique uses normality test statistic, homogeneity and T test with the aid of SPSS statistic 21. The results of this research shows that 1) there are differences in the results of student’s understanding of mitigation concepts by using audio-visual video media before and after treatment, 2) by using video, students give a positive respond on the learning process.